Comparison of Surgical Outcomes Following Primary Versus Revision Posterior Cervical Decompression and Fusion (PCDF). (16th November 2020) - Martini, Michael L; Neifert, Sean N; Gilligan, Jeffrey; Yuk, Frank; Zimering, Jeffrey H; Shuman, William; Chapman, Emily K; Gal, Jonathan; Caridi, John M
Abstract: INTRODUCTION: While previous studies have reported that revision surgery is a risk factor for certain adverse events during posterior spine surgery, no studies have specifically explored the risk and outcome profiles of revision versus primary surgeries approached posteriorly specifically in the cervical spine. METHODS: Patients undergoing posterior cervical fusions (63045, 63001, 63015, 22110, 22210, and 22600) and combined (posterior cervical fusion + 22554, 22551, or 63075) cervical approaches at a single institution from 2008 to 2016 were identified. Those who underwent prior posterior cervical surgery were compared against those undergoing primary PCDF for their perioperative outcomes and cost. Multivariable modeling controlled for age, sex, preoperative diagnosis, number of levels fused, surgical time, and estimated blood loss (EBL). RESULTS: Of the 1, 124 patients included in this study, 218 had a previous posterior cervical procedure. The revision patients were significantly younger (53.0 vs. 60.5, P < .0001) but had higher comorbidity burdens ( P < .0001). Even though the revision cohort had shorter surgical times (179 minutes vs. 206, P = .0005) and less mean segments fused (3.6 vs. 4.1, P < .0001), they also had higher blood loss (450 mL vs. 290, P = .07). Complication rates in primary (17.8%) and revision cohorts (21.6%) were not different on univariate (p = 0.20) or multivariate (p = 0.16) analyses. The primary cohort had higher rates of ICU stay (18.4% vs. 8.7%, P = .002) on multivariate analysis. Multivariate analysis revealed no significant differences between cohorts in length of stay (4.7 vs. 4.7 days, p = 0.96), nonhome discharge (Odds ratio: 0.71, 95%CI 0.46-1.1, p = 0.12), or direct costs (21, 014 vs. 22, 120, p = 0.48). CONCLUSION: Primary and revision PCDF procedures do not differ in terms of complication rate, hospitalization length, costs, or nonhome discharge.